2018
DOI: 10.1016/j.nmd.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of spinal muscular atrophy: Part 1: Recommendations for diagnosis, rehabilitation, orthopedic and nutritional care

Abstract: Spinal muscular atrophy (SMA) is a severe neuromuscular disorder due to a defect in the survival motor neuron 1 (SMN1) gene. Its incidence is approximately 1 in 11,000 live births. In 2007, an International Conference on the Standard of Care for SMA published a consensus statement on SMA standard of care that has been widely used throughout the world. Here we report a two-part update of the topics covered in the previous recommendations. In part 1 we present the methods used to achieve these recommendations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
748
0
104

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 681 publications
(861 citation statements)
references
References 97 publications
(140 reference statements)
9
748
0
104
Order By: Relevance
“…Some authors have also reported that adiposity is increased in nonambulatory, high‐functioning SMAII compared with low‐functioning, and ambulatory patients . Due to this altered BC and the lack of SMA‐specific growth charts, regular assessment of BC by DEXA has been included in the updated Standard of Care Recommendations to ensure proper nutritional management …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have also reported that adiposity is increased in nonambulatory, high‐functioning SMAII compared with low‐functioning, and ambulatory patients . Due to this altered BC and the lack of SMA‐specific growth charts, regular assessment of BC by DEXA has been included in the updated Standard of Care Recommendations to ensure proper nutritional management …”
Section: Discussionmentioning
confidence: 99%
“…16 Due to this altered BC and the lack of SMA-specific growth charts, regular assessment of BC by DEXA has been included in the updated Standard of Care Recommendations to ensure proper nutritional management. 17 Sproule et al 16 The high cost of orphan drugs may emerge as a limitation to guaranteeing the worldwide accessibility of treatments to all SMA patients, 18 and the need to predict individual response or to identify rules to stop or switch treatment to tailor therapy to patients will increase over time. There is a strong need to identify informative clinical and laboratory biomarkers that may allow monitoring of disease progression and may predict responders.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing is considered as the criterion standard to confirm the diagnosis of SMA. The test detects homozygous deletions or mutations of the SMN1 gene . Until 2017, no treatment was available for SMA, and management consisted of supportive measures: providing adequate nutrition and respiratory assistance, and preventing complications of weakness.…”
mentioning
confidence: 99%
“…Type 1 spinal muscular atrophy (SMA) is the most clinically severe form of the disease, characterized by a deficit of the SMN‐1 protein. Symptom onset occurs before age 6 months, and patients have profound weakness; in untreated patients, death occurs before age 2 years and is generally attributed to respiratory causes . This year, two breakthrough articles were published in the New England Journal of Medicine describing promising genetic therapies.…”
Section: Introductionmentioning
confidence: 99%